{-# OPTIONS --without-K --safe #-}
open import Algebra
module Algebra.Properties.CommutativeMonoid
{g₁ g₂} (M : CommutativeMonoid g₁ g₂) where
open import Algebra.Operations.CommutativeMonoid M
open import Algebra.Solver.CommutativeMonoid M
open import Relation.Binary as B using (_Preserves_⟶_)
open import Function
open import Function.Equality using (_⟨$⟩_)
open import Data.Product
open import Data.Nat using (ℕ; zero; suc)
open import Data.Fin using (Fin; zero; suc)
open import Data.List as List using ([]; _∷_)
import Data.Fin.Properties as FP
open import Data.Fin.Permutation as Perm using (Permutation; Permutation′; _⟨$⟩ˡ_; _⟨$⟩ʳ_)
open import Data.Fin.Permutation.Components as PermC
open import Data.Table as Table
open import Data.Table.Relation.Binary.Equality as TE using (_≗_)
open import Data.Unit using (tt)
import Data.Table.Properties as TP
open import Relation.Binary.PropositionalEquality as P using (_≡_)
open import Relation.Nullary using (yes; no)
open import Relation.Nullary.Negation using (contradiction)
open import Relation.Nullary.Decidable using (⌊_⌋)
open CommutativeMonoid M
renaming
( ε to 0#
; _∙_ to _+_
; ∙-cong to +-cong
; ∙-congˡ to +-congˡ
; ∙-congʳ to +-congʳ
; identityˡ to +-identityˡ
; identityʳ to +-identityʳ
; assoc to +-assoc
; comm to +-comm
)
open import Algebra.FunctionProperties _≈_
open import Relation.Binary.Reasoning.Setoid setoid
module _ {n} where
open B.Setoid (TE.setoid setoid n) public
using ()
renaming (_≈_ to _≋_)
te rn.
sumₜ-remove : ∀ {n} {i : Fin (suc n)} t → sumₜ t ≈ lookup t i + sumₜ (remove i t)
sumₜ-remove {_} {zero} t = refl
sumₜ-remove {suc n} {suc i} t′ =
begin
t₀ + ∑t ≈⟨ +-congˡ (sumₜ-remove t) ⟩
t₀ + (tᵢ + ∑t′) ≈⟨ solve 3 (λ x y z → x ⊕ (y ⊕ z) ⊜ y ⊕ (x ⊕ z)) refl t₀ tᵢ ∑t′ ⟩
tᵢ + (t₀ + ∑t′) ∎
where
t = tail t′
t₀ = head t′
tᵢ = lookup t i
∑t = sumₜ t
∑t′ = sumₜ (remove i t)
sumₜ-cong-≈ : ∀ {n} → sumₜ {n} Preserves _≋_ ⟶ _≈_
sumₜ-cong-≈ {zero} p = refl
sumₜ-cong-≈ {suc n} p = +-cong (p _) (sumₜ-cong-≈ (p ∘ suc))
sumₜ-cong-≡ : ∀ {n} → sumₜ {n} Preserves _≗_ ⟶ _≡_
sumₜ-cong-≡ {zero} p = P.refl
sumₜ-cong-≡ {suc n} p = P.cong₂ _+_ (p _) (sumₜ-cong-≡ (p ∘ suc))
sumₜ-idem-replicate : ∀ n {x} → _+_ IdempotentOn x → sumₜ (replicate {n = suc n} x) ≈ x
sumₜ-idem-replicate zero idem = +-identityʳ _
sumₜ-idem-replicate (suc n) {x} idem = begin
x + (x + sumₜ (replicate {n = n} x)) ≈⟨ sym (+-assoc _ _ _) ⟩
(x + x) + sumₜ (replicate {n = n} x) ≈⟨ +-congʳ idem ⟩
x + sumₜ (replicate {n = n} x) ≈⟨ sumₜ-idem-replicate n idem ⟩
x ∎
sumₜ-zero : ∀ n → sumₜ (replicate {n = n} 0#) ≈ 0#
sumₜ-zero n = begin
sumₜ (replicate {n = n} 0#) ≈⟨ sym (+-identityˡ _) ⟩
0# + sumₜ (replicate {n = n} 0#) ≈⟨ sumₜ-idem-replicate n (+-identityˡ 0#) ⟩
0# ∎
∑-distrib-+ : ∀ n (f g : Fin n → Carrier) → ∑[ i < n ] (f i + g i) ≈ ∑[ i < n ] f i + ∑[ i < n ] g i
∑-distrib-+ zero f g = sym (+-identityˡ _)
∑-distrib-+ (suc n) f g = begin
f₀ + g₀ + ∑fg ≈⟨ +-assoc _ _ _ ⟩
f₀ + (g₀ + ∑fg) ≈⟨ +-congˡ (+-congˡ (∑-distrib-+ n _ _)) ⟩
f₀ + (g₀ + (∑f + ∑g)) ≈⟨ solve 4 (λ a b c d → a ⊕ (c ⊕ (b ⊕ d)) ⊜ (a ⊕ b) ⊕ (c ⊕ d)) refl f₀ ∑f g₀ ∑g ⟩
(f₀ + ∑f) + (g₀ + ∑g) ∎
where
f₀ = f zero
g₀ = g zero
∑f = ∑[ i < n ] f (suc i)
∑g = ∑[ i < n ] g (suc i)
∑fg = ∑[ i < n ] (f (suc i) + g (suc i))
∑-comm : ∀ n m (f : Fin n → Fin m → Carrier) → ∑[ i < n ] ∑[ j < m ] f i j ≈ ∑[ j < m ] ∑[ i < n ] f i j
∑-comm zero m f = sym (sumₜ-zero m)
∑-comm (suc n) m f = begin
∑[ j < m ] f zero j + ∑[ i < n ] ∑[ j < m ] f (suc i) j ≈⟨ +-congˡ (∑-comm n m _) ⟩
∑[ j < m ] f zero j + ∑[ j < m ] ∑[ i < n ] f (suc i) j ≈⟨ sym (∑-distrib-+ m _ _) ⟩
∑[ j < m ] (f zero j + ∑[ i < n ] f (suc i) j) ∎
sumₜ-permute : ∀ {m n} t (π : Permutation m n) → sumₜ t ≈ sumₜ (permute π t)
sumₜ-permute {zero} {zero} t π = refl
sumₜ-permute {zero} {suc n} t π = contradiction π (Perm.refute λ())
sumₜ-permute {suc m} {zero} t π = contradiction π (Perm.refute λ())
sumₜ-permute {suc m} {suc n} t π = begin
sumₜ t ≡⟨⟩
lookup t 0i + sumₜ (remove 0i t) ≡⟨ P.cong₂ _+_ (P.cong (lookup t) (P.sym (Perm.inverseʳ π))) P.refl ⟩
lookup πt (π ⟨$⟩ˡ 0i) + sumₜ (remove 0i t) ≈⟨ +-congˡ (sumₜ-permute (remove 0i t) (Perm.remove (π ⟨$⟩ˡ 0i) π)) ⟩
lookup πt (π ⟨$⟩ˡ 0i) + sumₜ (permute (Perm.remove (π ⟨$⟩ˡ 0i) π) (remove 0i t)) ≡⟨ P.cong₂ _+_ P.refl (sumₜ-cong-≡ (P.sym ∘ TP.remove-permute π 0i t)) ⟩
lookup πt (π ⟨$⟩ˡ 0i) + sumₜ (remove (π ⟨$⟩ˡ 0i) πt) ≈⟨ sym (sumₜ-remove (permute π t)) ⟩
sumₜ πt ∎
where
0i = zero
πt = permute π t
∑-permute : ∀ {m n} f (π : Permutation m n) → ∑[ i < n ] f i ≈ ∑[ i < m ] f (π ⟨$⟩ʳ i)
∑-permute = sumₜ-permute ∘ tabulate
select-transpose : ∀ {n} t (i j : Fin n) → lookup t i ≈ lookup t j → ∀ k → (lookup (select 0# j t) ∘ PermC.transpose i j) k ≈ lookup (select 0# i t) k
select-transpose _ i j e k with k FP.≟ i
... | yes p rewrite P.≡-≟-identity FP._≟_ {j} P.refl = sym e
... | no ¬p with k FP.≟ j
... | no ¬q rewrite proj₂ (P.≢-≟-identity FP._≟_ ¬q) = refl
... | yes q rewrite proj₂ (P.≢-≟-identity FP._≟_
(¬p ∘ P.trans q ∘ P.sym)) = refl
sumₜ-select : ∀ {n i} (t : Table Carrier n) → sumₜ (select 0# i t) ≈ lookup t i
sumₜ-select {suc n} {i} t = begin
sumₜ (select 0# i t) ≈⟨ sumₜ-remove {i = i} (select 0# i t) ⟩
lookup (select 0# i t) i + sumₜ (remove i (select 0# i t)) ≡⟨ P.cong₂ _+_ (TP.select-lookup t) (sumₜ-cong-≡ (TP.select-remove i t)) ⟩
lookup t i + sumₜ (replicate {n = n} 0#) ≈⟨ +-congˡ (sumₜ-zero n) ⟩
lookup t i + 0# ≈⟨ +-identityʳ _ ⟩
lookup t i ∎
sumₜ-fromList : ∀ xs → sumₜ (fromList xs) ≡ sumₗ xs
sumₜ-fromList [] = P.refl
sumₜ-fromList (x ∷ xs) = P.cong (_ +_) (sumₜ-fromList xs)
sumₜ-toList : ∀ {n} (t : Table Carrier n) → sumₜ t ≡ sumₗ (toList t)
sumₜ-toList {zero} _ = P.refl
sumₜ-toList {suc n} _ = P.cong (_ +_) (sumₜ-toList {n} _)